Investigation of occupational noise annoyance in a wind turbine power plant - Monazzam, Mohammad R; Zakerian, Seyed A; Kazemi, Zeinab; Ebrahimi, Mohammad H; Ghaljahi, Maryam; Mehri, Ahmad; Afkhaminia, Farzaneh; Abbasi, Milad (Journal of low frequency noise, vibration, and active control, 2019)
Noise, emitted by wind turbines, is one of the main health risk factors which has been recently considered in many researches. Noise annoyance is among the most important human responses to noise. The aim of this work was to modeling of annoyance due to noise at workplace coming from wind turbines in workers. All workers of a wind power plant consisted the study sample. The equivalent noise level was measured using a task-based method. Moreover, data related to noise annoyance and noise sensitivity were acquired by standardized methods. Based on the results, noise exposure, noise sensitivity, visibility, age, and experience affected noise annoyance. According to path analysis, the most indirect and direct effect on noise annoyance were attributed to noise exposure. Age, sensitivity, and noise exposure were positively associated to annoyance. It can be concluded that there is a significant relationship between age, experience, sensitivity to noise, and exposure to the wind turbine noise with noise annoyance.